PENGARUH CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN FRESHCARE DI KOTA DENPASAR - Gusti Ayu Rinawati; Anak Agung Putu Agung; Ni Putu Nita Anggraini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
Economic growth and changes as well as increasingly rapid business activities require companies to develop marketing strategies to attract and retain consumers, one of which is by utilizing celebrity endorsers in promoting their products. In addition, thebrand imagewill determine the purchase decision of a product. This study aims to determine the effect of celebrity endorsers and brand image onpurchasing decisions freshcare in Denpasar City. The sample in this study amounted to 60 people who have usedproducts freshcare. Determination of the sample using amethod purposive sampling. The analytical tool used is multiple linear regression analysis using the SPSS program. The results showed that the results ofdetermination celebrity endorser and brand image amounted to 0.631 or 63.1%. the remaining 36.9% is explained by other variables that are not included in the model or research. So it can be concluded that celebrity endorser and brand image have a positive and significant effect on purchasing decisions